The Pentagon's new map : war and peace in the twenty-first century - Barnett, Thomas P. M. (New York : G.P. Putnam's Sons, 2004)
Military strategist Barnett provides a cutting-edge approach to globalization that combines security, economic, political, and cultural factors to predict and explain the nature of war and peace in the twenty-first century. Building on the works of Thomas L. Friedman and Francis Fukuyama, and then taking a leap beyond, this book offers hope at a crucial yet uncertain time in history.--From publisher description.
New rule sets -- The rise of the'lesser includeds' -- Disconnectedness defines danger -- The core and the gap -- The new ordering principle -- The global transaction strategy -- The myths we make -- Hope without guarantees.
Includes bibliographical references and index.
Keywords: World politics -- 1989-; United States -- Military policy